Settlement Pattern Morphology of Ampera Village - Yenny Novianti; Armelia Dafrina; Fikri Azmi Arta (Jurnal Arsitektur, 2023)
Kampung Ampera is one of the traditional settlements in the modern era and still maintains its customs. The Malay ethnicity is a characteristic of the people of Kampung Ampera. A settlement formed for the royal, colonial and modern eras. This settlement pattern is interesting to study because its living is part of historical growth and a form of settlement pattern that continues to grow and develop all this time. Not only that, the existence of a settlement pattern that persists with the traditional settlement pattern is the identity of the Malay community's settlement pattern. The formulation of the problem studied is the morphology of settlement patterns in the three periods and the factors that influence changes in their development. This research aims to identify the morphology of settlement patterns and the factors that affect them. This research is a qualitative descriptive study with an explanatory approach, showing the perspective of looking for an explanation of how this phenomenon can occur based on facts. The analysis technique used in settlement morphology is mapping settlement patterns in the royal (1750-1860), colonial (1860-1870), and modern (1900-present) periods. The morphological study of the settlements of Kampung Ampera includes, namely: land use, building typology, road network (linkage), and plot pattern (district). The study found that the morphology pattern spread linearly following the original river network to become a road network, the effect factor in the settlement was the view through the ecistic element factors.